Farmers Behavior In Integrated Rice Crops Management In The Rawa Lebak Agroecosystem: Perilaku Petani Dalam Pengelolaan Tanaman Terpadu Padi Di Agroekosistem Rawa Lebak - Maya Dhania Sari; Bunaiyah Honorita; Dedeh Hadiyanti (Program Studi Agribisnis Universitas Sumatera Selatan, 2021)
Abstract Rice productivities in the swamp radish area is still in low category. It needs to introduce technology innovation through integrated crop management approach. Adopting technology innovation process needs farmer’s behaviour changing. Farming instructor has strategic role in changing of farmer behaviour. There are many methods can be used, one of them is Aplply Experiment in effort technology dissemination Indonesian Agency for Agricultural Research and Development, do a studying applicating swamp rice cultivation to improve farmer behaviour. This paper aim to (1) to measure farmer’s knowledge and behaviour in swamp rice cultivation using PTT approach. (2) to evaluate farmer’s applying level in rice swamp cultivation using PPT approach. (3) to analyse relation between farmer’s knowledge and behaviour in rice swamp cultivation using PTT approach. This research has been done on December 2020 in Pemulutan village I, Ogan Komering Ilir district using survey method and interview using questioner. Being analysed descriptively and non-parametric Spearman Rank correlation. the result shows that most of respondents has known and agree with swamp rice cultivation technology by PTT approach exception in fertilization frequency and fertilization based on PUTR and only 40% and 30% farmers know about each component . Most farmer’s absorbing level is in trying level and just few reach applied level. Spearman rank Relation test result shows a significant relation between knowledge and farmer’s behaviour with relation direction positively with correlation coefficient is 1,00 and signification number is 0,000.